2021
DOI: 10.1063/4.0000045
|View full text |Cite
|
Sign up to set email alerts
|

Development of membrane-insertable lipid scrambling peptides: A time-resolved small-angle neutron scattering study

Abstract: Phospholipid transbilayer movement (flip-flop) in the plasma membrane is regulated by membrane proteins to maintain cell homeostasis and interact with other cells. The promotion of flip-flop by phospholipid scramblases causes the loss of membrane lipid asymmetry, which is involved in apoptosis, blood coagulation, and viral infection. Therefore, compounds that can artificially control flip-flop in the plasma membrane are of biological and medical interest. Here, we have developed lipid scrambling transmembrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The peptide indolicidin speeds up lipid exchange between vesicles while also making them grow [ 250 ], as do the antimicrobial peptides Aurein 1.2, LL-37, and Lacticin Q [ 251 ] Other peptides have a similar effect [ 252 , 253 , 254 ]. A series of peptides designed to scramble lipids in a bilayer was studied by Nakao and coworkers using SANS and contrast-matching methods [ 255 ]. By tracking the integrated intensity in a specific q -range, they were able to measure the rate of change in the neutron scattering contrast and therefore the lipid exchange.…”
Section: Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The peptide indolicidin speeds up lipid exchange between vesicles while also making them grow [ 250 ], as do the antimicrobial peptides Aurein 1.2, LL-37, and Lacticin Q [ 251 ] Other peptides have a similar effect [ 252 , 253 , 254 ]. A series of peptides designed to scramble lipids in a bilayer was studied by Nakao and coworkers using SANS and contrast-matching methods [ 255 ]. By tracking the integrated intensity in a specific q -range, they were able to measure the rate of change in the neutron scattering contrast and therefore the lipid exchange.…”
Section: Examplesmentioning
confidence: 99%
“… Peptide-enhanced exchange of lipids in vesicles [ 255 ]. ( A ) The integrated intensity as a function of time showing that two peptides engineered to scramble the lipids in the bilayer (4SQ and 4EQ) cause greater lipid exchange than when no peptide is present.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene glycol (PEG) is known to induce the fusion of lipid vesicles and cells. The presence of PEG induces depletion attraction between large obstacles owing to the excluded volume effect, resulting in their aggregation. , As PEG indirectly causes attraction between vesicles, this technique can be used to analyze the properties of bilayers adjacent to each other without introducing docking reagents into the membrane. Here, we investigate lipid transfer between vesicles brought into proximity by PEG using time-resolved small-angle neutron scattering (TR-SANS), a technique first established by our group for evaluating interbilayer and transbilayer transfer (flip-flop) of lipids. The thermodynamic activation parameters of lipid transfer were derived from the temperature dependence of the transfer. Notably, the inclusion of PEG-conjugated lipids into the vesicles manipulated the interbilayer distance of the aggregated vesicles, which was quantitatively analyzed using SANS.…”
mentioning
confidence: 99%
“…We have demonstrated that time-resolved small-angle neutron scattering is an effective method for evaluating the intervesicular transfer and flip-flop of phospholipids. This technique has been used to measure not only the spontaneous transfer of phospholipids but also lipid transfer via phospholipid transfer proteins and flip-flop via synthetic or naturally occurring peptides. Since the transfer of phospholipids between membranes occurs by dissociation from the outer leaflet of the membrane, the energetic information on the outer leaflet of the bilayer can be extracted. In this study, this technique was applied to measure the lipid dissociation kinetics of vesicles of different sizes to evaluate the effect of membrane curvature on phospholipid stability in lipid bilayers.…”
mentioning
confidence: 99%